Right to be informed and informed consent in Dentistry: A critical look beyond law regulation - Esparza-Reyes, Estefanía; Beltrán Varas, Víctor; Beltrán Varas, Pamela (Acta Bioethica, 2020)
This article aims to make clear that the Chilean regulation of the right to be informed and informed consent in Dentistry is not sufficient for the proper exercise of such rights. To do this, it begins by describing this obligations, considering historical and doctrinal aspects. It continues to analyze the right to be informed and informed consent, emphasizing its purpose and usefulness. Subsequently, the current Chilean regulation on the matter is critically detailed, to finish exposing aspects of dental practice in the field of informed consent. Lastly, some solution proposals for overcoming the problems found are indicated.